Building resilience from risk: Interactions across ENSO, local environment, and farming systems on the desert north coast of Peru (1100BC–AD1460). (December 2022) - Caramanica, Ari
The arid desert coast of northern Peru has traditionally been viewed either as existing in stasis, or as experiencing punctuated change from sudden flood events, followed by a return to system equilibrium. Despite these environmental extremes, the region was home to agriculture-based societies for millennia, and the success of these farming systems is considered an early example of irrigation technology transforming marginal landscapes. However, a closer examination of the long-term human-environment history of the Chicama Valley, one of the largest valleys in the coastal region, demonstrates that this landscape is the product of protracted interactions across at least three systems: the local environment, El Niño Southern Oscillation (ENSO), and farming. Here, El Niño floods, typically considered high-risk events, are fundamental to local biodiversity and renewal, resulting in a desert ecosystem that is both robust and elastic. The prehispanic farmland known as the Pampa de Mocan (1100BC–AD1460), is presented as a case study to observe the co-evolution of agricultural technology and an ENSO-hyper-arid environment. This ancient farming system developed the capacity to toggle between sudden floodwater inputs and periods of water scarcity. Alongside water and soil conservation practices, prehispanic agriculturalists implemented technologies that were designed to mitigate El Niño flooding and incorporate its byproducts to supplement available resources. The convergence of these interacting systems on the Pampa de Mocan offers new insights into the role of risk in building resilience.